2023
DOI: 10.1007/s11869-023-01321-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of indoor air quality and their inter-association in hospitals of northern India—a cross-sectional study

Abstract: This study was commenced to evaluate the indoor and outdoor air quality concentrations of PM 2.5 , sub-micron particles (PM >2.5 , PM 1.0–2.5 , PM 0.50 –1.0 , PM 0.25–0.50 , and PM <0.25 ), heavy metals, and microbial contaminants along with their identification in three different hospitals of Lucknow City. The study was conducted from February 2022 to April 2022 in hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 65 publications
1
1
1
Order By: Relevance
“…A study conducted in three hospitals in Northern India demonstrated lower indoor PM 2.5 levels than outdoors. Their indoor PM 2.5 levels were correlated with outdoor levels like in our study and both those levels were higher than in our results [53]. IAQ of six hospitals in Lahore, Pakistan was studied.…”
Section: Comparison Of the Results Of Similar Past Studies With Our R...supporting
confidence: 73%
See 1 more Smart Citation
“…A study conducted in three hospitals in Northern India demonstrated lower indoor PM 2.5 levels than outdoors. Their indoor PM 2.5 levels were correlated with outdoor levels like in our study and both those levels were higher than in our results [53]. IAQ of six hospitals in Lahore, Pakistan was studied.…”
Section: Comparison Of the Results Of Similar Past Studies With Our R...supporting
confidence: 73%
“…Further studies shall determine such ceilings appropriate for OPDs and ETUs of large hospitals of Sri Lanka. Limited published evidence and our results show that IAQ of OPDs and ETUs of Sri Lankan teaching hospitals is generally better than IAQ of hospitals of neighboring South Asian countries [52][53][54].…”
Section: Discussionmentioning
confidence: 93%
“…The study's PM 1 is higher than the levels recorded for Indonesia (28.25 mg/m 3 ) and Cyprus (10 mg/m 3 ) by Syafei et al (2020) and Konstantinou et al (2022), respectively. The PM 2.5 levels reported in this study are significantly lower than those discovered in Bangladesh (159.0 mg/m 3 ), Saudi Arabia (1100.00 mg/m 3 ), China (222.0 mg/m 3 ) and India (149.4 mg/m 3 ) Zaman et al (2021), Niu, Guinot, Cao, Xu, and Sun (2015) and Taushiba et al (2023), respectively, but significantly higher than 69.28 mg/m 3 and 11.5 mg/m 3 by Abulude et al (2021) and Ezeonyejiaku, Okoye, Ezeonyejiaku, and Obiakor (2022), respectively. The PM 10 results from our investigation were lower than those of Salama and Berekaa (2016), Niu et al (2015), Filonchyk and Yan (2018) and Shafi and Khelif (2021) but higher than the one (54.9 mg/m 3 ) obtained by Oweisana, Gobo, Daka, and Ideriah (2021).…”
Section: Resultscontrasting
confidence: 68%